Amelioration of pancreatic fat accumulation in Japanese type 2 diabetes patients treated with sodium‐glucose cotransporter 2 inhibitors: a retrospective study. (8th February 2021) - Horii, Tomomi; Kozawa, Junji; Fujita, Shingo; Hosokawa, Yoshiya; Kimura, Takekazu; Fujita, Yukari; Tokunaga, Ayumi; Fukui, Kenji; Shimomura, Iichiro
Abstract: Background: Prior reports have suggested that pancreatic fat is related to type 2 diabetes. Sodium‐glucose co‐transporter‐2 (SGLT‐2) inhibitors are expected to reduce ectopic fat accumulation. Aim: This study assessed the effect of SGLT‐2 inhibitors on pancreatic and liver fat accumulations in patients with type 2 diabetes. Materials and Methods: Retrospective analyses of indices of pancreatic and liver fat accumulations were conducted in 22 type 2 diabetes outpatients who were receiving SGLT‐2 inhibitors for more than 12 weeks. The differences between the pancreatic (P) or liver (L) and splenic (S) computed tomography values were evaluated. Results: Fatty pancreas was defined as P−S < −8 Hounsfield Unit (HU), and the number of patients with fatty pancreas was 11 (50%). Fatty pancreas significantly improved after SGLT‐2 inhibitor use (median, −20.8; IQR, −34.8 to −14.3 HU vs. median, −14.6; IQR, −29.5 to −7.8 HU; p  = 0.041). Fatty liver was defined as L−S ≤ 3.9 HU, and the number of patients with fatty liver was 11 (50%). Fatty liver significantly improved after SGLT‐2 inhibitor use (median, −4.3; IQR, −23.0 to 3.0 HU vs. median, −0.7; IQR, −5.2 to 6.3 HU; p  = 0.016). Conclusion: Pancreatic fat and liver fat accumulations might be reduced after treatment with SGLT‐2 inhibitors in type 2 diabetes patients with intense cumulative fat depositions in these organs.